Effects of Training on Timbre Recognition and Appraisal by Postlingually Deafened Cochlear Implant Recipients - Gfeller, Kate; Witt, Shelley; Adamek, Mary; Mehr, Maureen; Rogers, Jenny; Stordahl, Julie; Ringgenberg, Shelly (Journal of the American Academy of Audiology, 2002)
The purpose of this study was to compare the effect of structured training on recognition and appraisal of the timbre (tone quality) of musical instruments by postlingually deafened cochlear implant recipients. Twenty-four implant users (Nucleus C124M) were randomly assigned to a control or a training group. The control group experienced only incidental exposure to music in their usual daily routine. The training group participated in 12 weeks of training delivered via a laptop computer in which they were introduced to excerpts of musical instruments representing three frequency ranges and four instrumental families. Those implant recipients assigned to the training group showed significant improvement in timbre recognition (p < .0001) and timbre appraisal (p < .02) compared to the control group. Correlations between timbre measures and speech perception measures are discussed.
Keywords: Cochlear implants; music; normal-hearing adults; timbre; tone quality